Regional government competition and incentives for commuting taxes and transport investments - Toon Vandyck; Stef Proost (European Regional Science Association (ERSA), 2011)
This paper discusses incentives for investments in transport infrastructure and commuting subsidies in a multi-region framework. Responsibilities of fiscal treatment of commuting expenses, public provision of road infrastructure and road pricing are distributed among different levels of government. The incentives of governments are discussed in a setting with commuting from a peripheral, less productive area to an urban agglomeration or city center. The interactions between investment in transport infrastructure, road pricing and commuting subsidies are analyzed. First, the optimal number of commuters from the point of view of the federation is derived in a first best situation. When a tax on labor is levied to finance the investment in transportation, a commuting subsidy can correct the labor tax distortion and the first best outcome can be obtained. However, when the peripheral region is in control of the transport policy and perceives its position as a dominant supplier of labor, the regional government will have an incentive to strategically restrict the number of commuters. This will lead to a commuting tax. In addition, there will be underinvestment in infrastructure investment. The city government faces different incentives. On the one hand, profits made in the city increase with the commuting flow. Assuming profits are captured locally, the city thus benefits from a higher number of commuters. On the other hand, the city can raise tax revenues by taxing commuters. Therefore, tax exporting behavior can be one of the drivers of the city's transport policy. The result is a situation where the city invests in transport infrastructure to attract commuters and sets a tax on commuters to raise government revenues. We show that the intensity of the regional strategic behavior is affected by firm ownership structure, the number of labor-supplying regions and the revenue-sharing mechanism in the federation. The paper also looks into vertical tax competition and identifies possibilities for the federal government to correct the incentive structure through mechanism design. A numerical example illustrates the insights for commuting in Belgium.
Keywords: 330